A New Hypothesis on Aristoxenus' Works and the Birth of the Legend of Epaminondas - Tufano, Salvatore (Polskie Towarzystwo Filologiczne, 2023)
A New Hypothesis on Aristoxenus' Works and the Birth of the Legend of Epaminondas Nep. Epam. 2, 1–2, a list of Epaminondas’ teachers, offers information derived from a lost work by Aristoxenus, who may have written a Life of Epaminondas. The hypothesis rests on a comparison with the extant biographical materials on Aristoxenus and with the earliest reception of Epaminondas’ musical and philosophical education. Besides, I contend that Aristoxenus is a reliable source for the early years of Epaminondas’ life and, as such, the tradition that is based on Aristoxenus should be trusted in the reconstruction of Epaminondas’ early years.